Peningkatan hasil belajar PKn melalui model pembelajaran role playing pada siswa kelas V SD Negeri 1 Serenan Juwiring Klaten - Sri Maryatun (Universitas Sebelas Maret, 2020)
Abstract. The learning process of Civics in SD Negeri 1 Serenan Juwiring Klaten rarely uses learning methods that attract the attention and activeness of all students in the class. The purpose of this study was to investigate efforts to improve Civics learning outcomes through role playing learning models in fifth grade students of SD Negeri 1 Serenan Juwiring Klaten in the 2017/1988 academic year. This research is a classroom action research (CAR) with research into subjects becoming fifth grade students of SD 1 Serenan Juwiring Klaten for the 2017/2018 academic year. Data collection methods used in this study were test, interview and observation methods. The collected data were analyzed by descriptive analysis. This can be seen from the test results that have increased at the end of the first cycle test the average valueof students is 75.07 and in the second cycle the average value is 84.07.Kata kunci: experimental method, role playing, elementary school